(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the resulting coronavirus disease 2019 (Covid-19) have afflicted tens of millions of people in a worldwide pandemic. The most reliable approach to stop the spread of infectious illnesses is through vaccination. Safe and effective vaccines are needed urgently.Methods: The study had eighty-one (81) participants ranging from 18 to 66 years old who were recently injected with COVID-19 mRNA Pfizer/BioNTech [BNT162b2] vaccines. They received two vaccine doses of 30 μg, 0.3 mL injections twenty-one (21) days apart. Before the first vaccination, blood samples were collected. This procedure was repeated on days 7-10 following the first immunization, and on 7–10 days following the second dosage. All samples were tested for IFN-γ using a High Sensitivity Human ELISA Kit corresponding to each marker (Elabscience/United State).Results: Compared to before vaccination and the first dosage, IFN-g levels were higher after the second dose.Conclusions: Our study demonstrated that vaccinations caused Th1 biases in all groups.